1995
DOI: 10.1207/s15327558ijbm0201_3
|View full text |Cite
|
Sign up to set email alerts
|

Patient expectations and postoperative depression, anxiety, and psychosocial adjustment after temporal lobectomy: A prospective study

Abstract: This study examined the effects of patient expectations on short-term postoperative psychological adjustment alter surgery for epilepsy. Twenty-seven subjects (17 operative, 10 nonoperative controls) agreed to participate. A prospective longitudinal design assessed whether changes in psychosocial functioning had occurred at a mean of 7 weeks after surgery relative to the presurgical assessment. The study also examined the relation between postoperative psychosocial adjustment and preoperative patient expectati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
19
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 27 publications
5
19
0
Order By: Relevance
“…Many women expressed the belief that they could personally control the cancer and keep it from coming back. Since that time, we have uncovered similar findings in studies with people infected by HIV or with AIDS (Reed, Kemeny, Taylor, Wang, & Visscher, 1994) and with heart disease (Helgeson & Taylor, 1993); other researchers have also observed that life-threatening events often confer surprising advantages (Leedham, Meyerowitz, Muirhead, & Frist, 1995;Petrie, Buick, Weinman, & Booth, in press;Rose, Derry, & McLachlan, 1995;Shifren, 1996). Despite the fact that these beliefs were inconsistent with objective medical evidence, they were associated with the criteria normally associated with mental health and not with psychological distress (Taylor, 1983;Taylor et al, 1984).…”
supporting
confidence: 79%
“…Many women expressed the belief that they could personally control the cancer and keep it from coming back. Since that time, we have uncovered similar findings in studies with people infected by HIV or with AIDS (Reed, Kemeny, Taylor, Wang, & Visscher, 1994) and with heart disease (Helgeson & Taylor, 1993); other researchers have also observed that life-threatening events often confer surprising advantages (Leedham, Meyerowitz, Muirhead, & Frist, 1995;Petrie, Buick, Weinman, & Booth, in press;Rose, Derry, & McLachlan, 1995;Shifren, 1996). Despite the fact that these beliefs were inconsistent with objective medical evidence, they were associated with the criteria normally associated with mental health and not with psychological distress (Taylor, 1983;Taylor et al, 1984).…”
supporting
confidence: 79%
“…This implies that, in the present study, unfulfilled expectations for the recovery period were not related to lower levels of well-being. This has also been highlighted in research on the importance of expectations in medical intervention (Andrykowski et al 1995;Rose et al 1995;Koller et al 2000;Holzner et al 2001). Altogether, most of the participants in the present studyslightly more than 1 year after treatment -had a feeling of satisfaction with their current life.…”
Section: Discussionsupporting
confidence: 76%
“…Also, positive changes have a great potential to balance the negative changes associated with cancer (Dow et al 1996). This has also been highlighted in research on the importance of expectations in medical intervention (Andrykowski et al 1995;Rose et al 1995;Koller et al 2000;Holzner et al 2001). For some, these positive changes made them feel that their lives had turned out better than expected.…”
Section: Discussionmentioning
confidence: 95%
“…It may be that patients with milder PD have greater expectations for restoration of function (78) and thus, might be at greater risk of having unmet expectations. Similarly, unmet seizure reduction and psychosocial improvement expectations are associated with lesser postoperative satisfaction and poorer psychosocial outcome after ablative epilepsy surgery (79)(80)(81), and the issue of pre-operative expectations and satisfaction with DBS in MS has also been addressed (82).…”
Section: Purposes Of Pre-operative Neuropsychological Evaluationmentioning
confidence: 99%
“…Depression is the most common psychiatric comorbidity in patients with epilepsy, and 40 to 60% of persons with TLE may have depression (152). Assessment of depression is of particular relevance in DBS candidates for at least three reasons: depression can exacerbate cognitive impairment in PD (153)(154)(155) and MS (156); depression has been associated with poorer surgical outcome in movement disorders (157); and pre-operative depression confers higher risk of continued depression after epilepsy surgery (81,158). Depression also compromises the patient's cooperation during surgery while awake and reduces resources to cope with peri-and postoperative stressors.…”
Section: Mood State and Behavioral Symptomsmentioning
confidence: 99%